PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA KELAS IV - Pardede, Dhea Omry Ananda; Simanjuntak, Eva Betty (Jurnal Merah Putih Sekolah Dasar, 2025)
The study was conducted with the aim of knowing student learning outcomes after using Wordwall media in fourth grade English lessons at SDN 033911 Belang Malum. The population of this study were fourth grade students of SDN 033911 Belang Malum and the sample in this study were 35 students. This type of research is quantitative research. This research method is Pre-experimental method with One Group Pre-test Post-test design. The techniques used in data collection are teacher interviews, test questions, and documentation. The results of this study indicate that there is an effect of using wordwall media on students' English learning outcomes. This is based on the average student Post-Test score of 83 higher than the Pre-Test average score of 59. The results of hypothesis testing using the paired sample T-test test found the sig. (2- tailed) of 0.000 The sig value. (2-tailed) < 0.05 or 0.000 < 0.05. This shows that there is a significant effect of using Wordwall learning media on the English learning outcomes of SDN 033911 Belang Malum.